Ruptured testicular abscess: a rare complication of epididymo-orchitis - Lee, C. Y.; Syazwan, Abu; Omar, Syed F. S.; Anuar, Syahril; Ab Rashid, Islah Munjih; Ghazali, Hamid (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Epididymo-orchitis is a medical condition characterised by inflammation of epididymis and testis which is a common urological diagnosis encountered by healthcare professionals. Misdiagnosis and under treatment can lead to poor outcome such as infarction and abscess formation. We presented a 33-year-old man, with no known medical illness, presented with one-week history of left testicular pain, swelling and fever. He was commenced on Amoxicillin by his general practitioner. Physical examination showed left swollen and tender testis and normal right testis. Investigations showed an elevated white cell count (WCC) 41.3x103 /L and colour doppler ultrasound (USG) testes showed left epididymo-orhitis. He was admitted and treated with IV Unasyn® (Ampicillin+Sulbactam) for 5 days. His symptoms improved, and he discharged home well with one week oral Unasyn®. He represented 2 weeks later with worsening left scrotal swelling and pain. Clinical examination found a swollen, tender and erythematous scrotum with 1x1cm defect in the left scrotum with purulent discharge. He underwent operation incision and drainage of left scrotum and left orchidectomy. Post-operatively he recovered well. Histopathology reported as epididimoorchitis with abscess, necrosis and perforation. As a conclusion, testicular rupture and abscess formation secondary to epididymo-orchitis is an uncommon reported complication. Immediate recognition and treatment is crucial as a delayed diagnosis can lead to sepsis and infertility.